SISTEM INFORMASI VISUALISASI PEMETAAN LOKASI USAHA KECIL MENENGAH DI KECAMATAN BANGIL BERBASIS WEB - Achmad Efendi; Teguh Pradana (STMIK YADIKA BANGIL, 2016)
Abstract : Currently SMEs in Indonesia per year has a number of very rapid growth with employment reached more than 90% of the total workforce in Indonesia is dominated by young people and women. SMEs in Indonesia are able to donate progress of national economic growth with exports. Small and Medium Enterprises SMEs is an abbreviated term referring to a type of small business that has a net worth of Rp 200 million, excluding land and buildings. And a stand-alone business.This application is the introduction of innovation in SMEs in the urban area Bangil digitally through a website. Will be on show on the short profile, various products from each - each SME that has been recorded.Keywords: ukm, php, mysql, visualization